2015
DOI: 10.4103/1117-1936.170740
|View full text |Cite
|
Sign up to set email alerts
|

Impact of basic life support training on the knowledge of basic life support in a group of Nigerian Dental Students

Abstract: The results of this study suggest that the group of dental students' knowledge of BLS was very poor prior to the BLS training. The study also showed that the BLS training had a positive influence on the BLS knowledge of the participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
7
2
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 3 publications
5
7
2
4
Order By: Relevance
“…Inadequate level of BLS knowledge amongst nurses was found in studies conducted in United States of America (USA) [8], the United Kingdom (UK) [7], Finland [9] and Ireland [3]. Similar trend was also observed in countries like Bahrain [10], Greece [11], Nigeria [12] South Africa [13] and Ethiopia [14] but to our knowledge no previous study has been conducted in Eritrea to determine the effect of BLS training on the knowledge of nurses.…”
Section: Introductionsupporting
confidence: 72%
See 2 more Smart Citations
“…Inadequate level of BLS knowledge amongst nurses was found in studies conducted in United States of America (USA) [8], the United Kingdom (UK) [7], Finland [9] and Ireland [3]. Similar trend was also observed in countries like Bahrain [10], Greece [11], Nigeria [12] South Africa [13] and Ethiopia [14] but to our knowledge no previous study has been conducted in Eritrea to determine the effect of BLS training on the knowledge of nurses.…”
Section: Introductionsupporting
confidence: 72%
“…This clearly indicate that majority of the nurses were not familiar with the resuscitation procedure. In contrast to this, a study done in Nigeria by [12] on dental students, found that all the respondents knew the full abbreviation of CPR.…”
Section: Knowledge Of Study Participants On Basic Life Supportcontrasting
confidence: 57%
See 1 more Smart Citation
“…However, the number of participants calling themselves qualified is still far beyond that of another study in which only 5.9% of the health professionals surveyed felt qualified. 16 On the other hand, this study showed that most participants already had participated in Basic Life Support (BLS) training courses when compared to other studies 8,10 in which professionals had never participated in similar training.…”
Section: Resultsmentioning
confidence: 54%
“…The Owojuyigbe et al (2015) study states that 75% of respondents obtained sufficient BLS knowledge after attending the training. 7 However, there are a number of studies that have not significantly decreased the value of knowledge after receiving the BLS training, namely the Bhatnagar et al (2017). It happened because of various factors that require further research.…”
Section: Resultsmentioning
confidence: 99%